Platypnoea–orthodeoxia syndrome exacerbated by kyphosis progression. (30th July 2018) - Iwai, Takamasa; Miyamoto, Takamichi; Miyazaki, Ryoichi; Nozato, Toshihiro
Abstract : This is a case of an 86-year-old woman with gradually progressive dyspnoea and hypoxaemia that occurred after a cardiac surgery. It was underdiagnosed for several years, but diagnosis was triggered by the finding of hypoxaemia even during supplemental oxygen administration when in the upright position, such as when taking a shower, that rapidly improved when the patient returned to the supine position. A thorough workup disclosed platypnoea–orthodeoxia syndrome (POS) associated with right-to-left shunting through a patent foramen ovale (PFO). Percutaneous closure of the PFO was performed. After treatment, the patient's arterial oxygen saturation gradually recovered to 98% on room air while she was in the sitting position and her symptoms disappeared. Reviewing this case retrospectively, we determined that the deviation of the spine with kyphosis progression had apparently proceeded as POS worsened over time. We therefore hypothesised that kyphosis progression had played a major role in the POS progression.